2007
DOI: 10.3892/or.18.4.885
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of TANGO in colon and hepatocellular carcinomas

Abstract: Abstract. The TANGO gene was originally identified as a new family member of the MIA gene family. The gene codes for a 14-kDa protein of so far unknown function. Recently, we identified TANGO as a tumor suppressor in malignant melanoma. In this study we evaluated TANGO transcription in different colon and hepatocellular carcinoma cell lines and tissue samples, to analyze whether loss of TANGO expression is a more general process in tumor development. TANGO was down-regulated or lost in all hepatocellular and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…MIA3, also referred to as ARNT or TANGO, belongs to the melanoma inhibitory activity gene family and may have a role in tumor suppression. 24,25 As with the case of rs1333049, the classic risk factors appear not to be related to the increased MI risks associated with rs17465637.…”
Section: Discussionmentioning
confidence: 99%
“…MIA3, also referred to as ARNT or TANGO, belongs to the melanoma inhibitory activity gene family and may have a role in tumor suppression. 24,25 As with the case of rs1333049, the classic risk factors appear not to be related to the increased MI risks associated with rs17465637.…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs17465637 on chromosome 1q41 is located in the MIA3 gene, which encodes melanoma inhibitor protein 3 required for export of collagen VII (COL7A1) from the endoplasmic reticulum (Saito et al, 2009), and appears to be a tumor suppressor of malignant melanoma (Arndt & Bosserhoff, 2007). MIA3 may be involved in facilitating the migration of monocytic cells through fibrinogene or human microvascular endothelial cells (Arndt et al, 2007), which may increase the risk of plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these studies also identified O-glycans on mammalian Tango1/Mia3 (26,27), suggesting that O-glycans may perform similar protective functions to control secretion in mammalian systems. Indeed, alterations in both Tango1/Mia3 and O-glycosylation have been associated with diseases of the mammalian gastrointestinal tract (5,6,28,29), which are typically characterized by loss of secretion, loss of mucous membrane formation, and increased diffusion barrier permeability. Interestingly, PGANT4 is most similar to the mammalian ppGalNAc-T10 (8), which is abundantly expressed in the digestive system (30).…”
Section: Resultsmentioning
confidence: 99%